Pengaruh Lokasi, Harga Dan Keberagaman Produk Terhadap Minat Beli Konsumen : Studi Kasus Pada Pasar Tradisional Gambir Kota Tebing Tinggi - Arfah, Yenni; Siregar, Wirda Ardilla (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims to determine the effect of location, price and product diversity on consumer buying interest (a case study on traders at Gambir Traditional Market, Tebing Tinggi City). The research method used is a quantitative method using SPSS version 25.00. The results of distributing questionnaires to the public are 96 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis (R2), hypothesis testing, namely T test and F test. The results of SPSS in this study, namely the location variable (X1) affect the interest variable buying (Y), Price Variable (X2) has no effect on buying interest (Y), Product Diversity (X3) has an effect on buying interest (Y) and Location (X1) is the most dominant variable affecting Buying interest (Y).